2020
DOI: 10.1002/chem.201905070
|View full text |Cite
|
Sign up to set email alerts
|

Influencing the Self‐Sorting Behavior of [2.2]Paracyclophane‐Based Ligands by Introducing Isostructural Binding Motifs

Abstract: Two isostructural ligands with either nitrile (Lnit) or isonitrile (Liso) moieties directly connected to a [2.2]paracyclophane backbone with pseudo‐meta substitution pattern have been synthesized. The ligand itself (Lnit) or its precursors (Liso) were resolved by HPLC on a chiral stationary phase and the absolute configuration of the isolated enantiomers was assigned by XRD analysis and/or by comparison of quantum‐chemical simulated and experimental electronic circular dichroism (ECD) spectra. Surprisingly, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 136 publications
0
6
0
Order By: Relevance
“…Interestingly, the only difference between them was the element on the nearest carbon of the chiral nitrogen: one was O and the other was S. Similar results were observed when the atoms or groups changed their position on the molecules. 82,83 For instance, Yashima and co-workers changed the sequence of amide (NHCO or CONH) on cyclohexane derivates and totally changed their assembly behaviour (Fig. 7b and c).…”
Section: Chirality Differencementioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the only difference between them was the element on the nearest carbon of the chiral nitrogen: one was O and the other was S. Similar results were observed when the atoms or groups changed their position on the molecules. 82,83 For instance, Yashima and co-workers changed the sequence of amide (NHCO or CONH) on cyclohexane derivates and totally changed their assembly behaviour (Fig. 7b and c).…”
Section: Chirality Differencementioning
confidence: 99%
“…Chan et al reported a series of terpyridine based multi-armed ligands that assembled with Cd 2+ into nanocapsules, 111 starlike structures, 28 triangles or hexagons. 111 Other structures like snowflake 112 and cage 83,113 were also achieved by varying the structure of ligands. Overall, this inspiring strategy has greatly expanded the ligand-based self-sorting assembly library, and was applicable in the synthesis of a metal complex with a controllable structure.…”
Section: Spatial Arrangementmentioning
confidence: 99%
“…The solid-state fluorescence emission maxima of the racemic ligand were observed at 448 nm upon excitation at λ ex = 419 nm, which can be ascribed to the π-π* and n-π* transitions. The main emission peaks occur at 486 nm for 1, 462 nm for 2, 472 nm for 3, and 492 nm for 4, exhibiting a red shift (38,14,24, and 44 nm) as compared with the racemic ligand, which indicates that the emission of 1-4 may presumably be associated with metal to ligand charge-transfer transitions (MLCT). [43] In fact, the different emissions are also related to other factors, such as the coordination environments of the metal ions or solvent molecules in different complexes, as well as the formation of different structural types.…”
Section: Luminescence Propertiesmentioning
confidence: 99%
“…[22] Mastering the self-sorting behavior is of utmost importance to cope with the immense structural complexity that such systems offer. [23][24][25][26][27] Thus the exploration and understanding of the factors that affect the structural self-assembly is essential for crystal engineers who design structures, in particular those of materials based on coordination networks with racemic ligands. recognition or self-discrimination of the ligand units.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation